Improving the Stability of Slopes with the Aid of Underground Houses. (2015) - Ilieş, Nicoleta-Maria; Moldovan, Ioana-Mădălina; Moldovan, Silivan-Valentin
Abstract: Low-rise residential constructions, developed on the slopes of urban settlements throughout the Transylvanian Plateau, are almost always facing the problem of landslides. Besides the benefits of the thermal efficiency of underground and semi-buried homes, the hypothesis that a house, together with its structural system, is capable to stabilize a slope appears to be very interesting. The purpose of the paper is to demonstrate how the structure of an underground house influences the stability of a slope.